Identification of sublattice damages in swift heavy ion irradiated N-doped 6H-SiC polytype studied by solid state NMR - Viswanathan, E.; Kanjilal, D.; Sivaji, K.; Ganapathy, Subramanian (Journal of Physical Chemistry B, 2011)
We have studied N-doped 6H-SiC in its pristine and Swift Heavy Ion (SHI) irradiated (150 MeV Ag12+ ions) forms by solid state Nuclear Magnetic Resonance (NMR) at 7.01 T using C-13 and Si-29 as probe nuclei under magic angle spinning. We show that increased levels of nitrogen doping, than used before, lead to the observation of Knight shifts emanating from an increase in electron density in the conduction band, which in C-13 far exceed those in Si-29 MAS spectra. We have rationalized the differential effects in the MAS spectra and site-dependent paramagnetic shifts in terms of the nitrogen doping at the A, B, and C lattice sites. N-doping has a profound effect on Si-29 spin-lattice relaxation, and the site-dependent relaxation behavior is attributed to a difference in conduction electron properties at the different lattice sites. Si-29 T-1 measurements serve to identify the sublattice damages in SHI irradiated 6H-SiC. By determining the spin-lattice relaxation rates as a function of the SHI irradiation ion fluences, the change in relaxation behavior is correlated to the damage production mechanism. The sublattice damage leads to discernable changes in the interaction between the mobile unpaired electrons in the conduction band and the nuclear site, which profoundly influence the NMR relaxation properties. Our relaxation studies also provide evidence for site-dependent localized effects and a decrease in carrier spin density in the conduction band for the SHI irradiated 6H-SiC.